The Effect of Bulk Depth and Irradiation Time on the Surface Hardness and Degree of Cure of Bulk-Fill Composites - Farahat F; Daneshkazemi AR; Hajiahmadi Z (Shiraz University of Medical Sciences, 2016)
Statement of Problem: For many years, application of the composite restoration with a thickness less than 2 mm for achieving the minimum polymerization contraction and stress has been accepted as a principle. But through the recent development in dental material a group of resin based composites (RBCs) called Bulk Fill is introduced whose producers claim the possibility of achieving a good restoration in bulks with depths of 4 or even 5 mm. Objectives: To evaluate the effect of irradiation times and bulk depths on the degree of cure (DC) of a bulk fill composite and compare it with the universal type. Materials and Methods: This study was conducted on two groups of dental RBCs including Tetric N Ceram Bulk Fill and Tetric N Ceram Universal. The composite samples were prepared in Teflon moulds with a diameter of 5 mm and height of 2, 4 and 6 mm. Then, half of the samples in each depth were cured from the upper side of the mould for 20s by LED light curing unit. The irradiation time for other specimens was 40s. After 24 hours of storage in distilled water, the microhardness of the top and bottom of the samples was measured using a Future Tech (Japan- Model FM 700) Vickers hardness testing machine. Data were analyzed statistically using the one and multi way ANOVAand Tukey's test (p = 0.050). Results: The DC of Tetric N Ceram Bulk Fill in defined irradiation time and bulk depth was significantly more than the universal type (p < 0.001). Also, the DC of both composites studied was significantly (p < 0.001) reduced by increasing the bulk depths. Increasing the curing time from 20 to 40 seconds had a marginally significant effect (p ≤ 0.040) on the DC of both bulk fill and universal studied RBC samples. Conclusions: The DC of the investigated bulk fill composite was better than the universal type in all the irradiation times and bulk depths. The studied universal and bulk fill RBCs had an appropriate DC at the 2 and 4 mm bulk depths respectively and using the recommended curing time of 40s can led to the slightly better value of DC in both composites.